Monocyte programmed death-ligand 1 upregulation in early post-out-of-hospital cardiac arrest is associated with increased risk of acute respiratory distress syndrome - Le An; Rui Shao; Chenchen Hang; Xingsheng Wang; Luying Zhang; Hao Cui; Jingfei Yu; Zhenyu Shan; Ziren Tang (Resuscitation Plus)
Background: Out-of-hospital cardiac arrest (OHCA) is a major public health problem. Acute respiratory distress syndrome (ARDS) is a common condition in OHCA patients. We investigated the relationship between the expression of programmed death-1 (PD-1) related molecules and the development and prognosis of ARDS. Methods: Between January 2021 and December 2023, post-resuscitated patients were screened for eligibility in the study. PD-1 related molecules expression was measured by flow cytometry at 48 h of admission in patients with OHCA. The prognostic variables were the development of ARDS during hospitalization and the 28-day patient mortality rate. We analyzed the relationship between the expression of PD-1-related molecules and the development of secondary ARDS in OHCA patients, and assessed the correlation of this expression with the prognosis of ARDS patients. Results: In total, 107 consecutive OHCA patients were enrolled in this study. The median age of the enrolled patients was 60 years, with an age range of 53 to 67 years, and 71 % were male. Among the cardiac arrest patients, 44.8 % had a cardiac etiology, 30.8 % were witnessed, 17.8 % received bystander CPR, and 66.4 % had an initial rhythm of asystole. Our results showed that only monocyte ligand programmed death ligand-1 (PD-L1) expression was significantly elevated in the ARDS group of OHCA patients (P < 0.001). Among patients with ARDS, the expression of PD-L1 on monocytes in non-survivors was significantly higher than in survivors (P < 0.05). The Receiver operating characteristic curves analysis demonstrates that monocyte PD-L1 expression has predictive potential for the development and prognosis of ARDS. Multivariate logistic regression analysis showed that monocyte PD-L1 expression was an independent predictor of mortality in OHCA patients with ARDS. Conclusions: This study indicates that patients with increased PD-L1 on monocytes after OHCA may be more likely to develop ARDS. The expression of PD-L1 on monocytes was an independent predictive factor for the incidence of ARDS and mortality rate in OHCA patients.